The impact of fencing training symmetrisation on simple reaction time - Johne, M. (Biomedical Human Kinetics, 2021)
Study aim: The symmetrisation of movements can be a way to develop individual coordinative skills, and to prevent the occur-rence of injuries. For this reason, in this study an attempt was made to evaluate and compare simple reaction time and movement time for épée fencers of different sports classes, and to determine the impact that three years of symmetrisation training and unilateral training have on the speed of reaction components and on dynamical asymmetry.